PENANA: AUDIO-VISUAL MEDIA TO IMPROVE ACROSTIC POETRY WRITING SKILLS - Resyi Abdul Gani; Rini Sri Indriani; Nur Hikmah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2024)
Interactive learning media strengthens user responses as quickly and often as possible, providing opportunities for students to control their learning pace and pay attention to coherent sequences assisted by audio-visual media penana, which can improve acrostic poetry writing skills. This research was conducted on July 25, 2023, with a total of 24 students consisting of 2 men and 22 women. This study aims to see how writing poetry, acrostic techniques assisted by audio-visual media, and penana applications can improve poetry writing skills using a qualitative approach and a classroom action research design following the Kemmis and Taggart model. The study was conducted in 3 cycles, where each cycle included 4 stages, namely planning, acting, observing, and reflecting, and involved 24 students in semester V. Data was obtained using observation, tests, non-tests, interviews, and documentation. The findings of this study suggest that the acrostic technique of poetry, assisted by audio-visual media, can help improve poetry writing skills. The results showed an increase in semester V students' poetry writing skills. This was evidenced by the classical completeness of the success of Indonesian grammar and literature skills cycle I by 71% with the criteria of